UTAUT Model Analysis on the Use of Siplah (Survey to BOSP Treasurers Under the Auspices of Cadisdikwil VII West Java Province) - Panji Mustika Muhammad; Dani Dagustani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Increasing technological progress in the world has helped people's activities, including upgrades related to technological adaptation. The reach and ease of digital accessibility is the result of adopting the latest technology. One of the activities in the world that applies digitalization is the buying and selling process, including PBJ (Procurement of Goods/Services) carried out by government agencies. This activity is regularly carried out, one of which is spending using BOSP (School Operational Assistance) funds at each state school, carried out using the SIPLah (System Information Procurement in Schools). The use of SIPLah was determined based on the Ministry of Education and Culture Regulation Number 14 of 2020 to safeguard the use of BOSP Funds. In line with its implementation, research efforts are needed regarding how good SIPLah technology is, so that it can be accepted by the BOSP Treasurer of each school as the main user. Among the latest research models that can be applied to determine the level of technological adaptation so that the BOSP Treasurer is willing to adopt SIPLah is the Unified Theory of Acceptance and Use of Technology (UTAUT). The research in this model consisted of four independent variables (Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions) used to test their influence on behavioral intentions and their consequences on use behavior. The research method used was a descriptive analysis of respondent responses and verification to determine the influence of all variables through path coefficients using census data. The respondents involved in the research were 57 treasurers of BOSP in the Bandung and Cimahi City areas, under the auspices of Cadisdikwil VII West Java. The results of the study concluded that the four independent variables influence behavioral intentions and have implications for use behavior. Suggestions based on the research results can be used by the Ministry of Education and Culture to improve SIPLah to make it more adaptive so that all transactions carried out by the BOSP Treasurer can use SIPLah.